Direct enhancement of intercomponent interactions in polyrotaxane and its pronounced effects on glass state properties. Issue 93 (3rd November 2021) - Kato, Kazuaki; Mizusawa, Tomoki; Ohara, Akihiro; Ito, Kohzo
Abstract : Intercomponent interactions in polyrotaxane glass influenced the mobility of the threading polymer confined in the glassy host framework, resulting in markedly different mechanical properties. Abstract : Strong interactions between the host cyclodextrin and the threading guest polymer were introduced by selective modifications to the polymer of a polybutadine-based polyrotaxane. The changes in the intercomponent interactions influenced the mobility of the threading polymer that was confined in the glassy host framework, resulting in different mechanical properties.